Ideas of education as basic guidelines for ensuring quality of life in modern conditions - F. R. Khatit; A. V. Leontyeva; T. N. Poddubnaya (Вестник Майкопского государственного технологического университета)
In the modern world, education is of great importance, since it is the main source of social progress. Changing technologies in the socio-economic sphere directly affect the transformation of the education sector throughout the world. The presented article is theoretical in nature and is devotedto the scientific problem of the transformation of education in modern sociocultural conditions.   The purpose of the research is to reveal the directions of transformation of education as basic guidelines for its quality in modern conditions.   The research methods used are analysis, theoretical generalization, forecasting.   The results of the research. The definition of “quality of education” has been revealed and the vectors of its development determined; the reasons that caused a serious transformation of the education sector in the world and in Russia have been argued. The drivers that determined the transformation of the educational institution at the present stage have been systematized.   Key conclusions: the quality of education is understood as a characteristic of the education system, reflecting the degree of compliance of the actual achieved educational results with regulatory requirements, social and personal expectations; the reasons facilitating the transformation of the education sector at present are: growing globalization, general digitalization, robotization, etc.; The leading drivers determining the development of education include: external, industrial and internal ones.